Pengaruh Kompensasi Financial dan Stres Kerja Terhadap Turnover Intention Melalui Komitmen Organisasional Sebagai Variabel Mediasi pada Rumah Sakit Sarkies ‘Aisyiyah Kudus - Frida Fitriani; Kertati Sumekar; Supriyono Supriyono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of financial compensation and work stress on turnover intention with organizational commitment as an intervening variable. The data of this study used primary data in the form of questionnaires. The sampling method used purposive sampling and obtained a sample of 149 respondents. The data analysis used in this study was the structural equation model. The results of this study stated that financial compensation had a positive and significant effect on organizational commitment, work stress had a negative and significant effect on organizational commitment, financial compensation did not affect turnover intention, work stress had a positive and significant effect on turnover intention, organizational commitment had a negative and significant effect on turnover intention.